SEKURITISASI ISU MIGRASI DI POLANDIA : KEAMANAN NASIONAL ATAU SOLIDARITAS REGIONAL? - Makhroja, Mega Nisfa (Department of International Relations, University of Mataram, 2020)
Abstract This paper analyzes the policy of the Polish government in responding to the migration crisis in Europe. The Polish government decided not to accommodate more refugees from Africa and the Middle East for reasons of national security. The homogeneous character of society will be disturbed by massive waves of migration. On the other hand, as a member of the European Union, Poland has an obligation to follow the scheme of the distribution of refugee quota to his country. Using the securitization analysis of non-traditional security issues, this research will describe the securitization process that starts with securitizing actors, speech acts, existential threats, referent objects, audiences, and functional actors. The securitization process is carried out by constructing an issue that was not originally a security issue to a security issue. The findings of this study indicate that the Polish government's policy of rejecting refugees is a form of securitization of the issue of migration as a threat to its national security.